Bandwidth enhancement of MIR emission in Yb3+/Er3+/Dy3+ triply doped fluoro-tellurite glass. (8th February 2017) - Balaji, Sathravada; Allu, Amarnath R; Biswas, Kaushik; Gupta, Gaurav; Ghosh, Debarati; Annapurna, Kalyandurg
Abstract: Enhanced bandwidth of MIR emission from Yb 3+ /Er 3+ /Dy 3+ triply doped low phonon oxide glass system has been reported in this work. With considerable gain cross-section, the MIR emission bandwidth can be stretched from 2600 to 3100 nm ( 500 nm) which is practically not possible to obtain from Er 3+ or Dy 3+ ions singly doped systems. Co-doping of Dy 3+ ions not only quenches the unfavourable visible up-converted emissions from Er 3+ ions but also mitigates the prominent 1.5 µ m emission. A broad MIR emission on superimposition of Er 3+ 2.76 µ m and Dy 3+ 2.95 µ m emissions was obtained owing to the efficient energy transfer (ET) Yb 3+ → Er 3+ → Dy 3+ upon 980 nm excitation. The present glasses can be fiberized to develop compact and tunable MIR solid state fiber laser sources.